Clickable artificial heme‐peroxidases for the development of functional nanomaterials. (26th June 2020) - Zambrano, Gerardo; Chino, Marco; Renzi, Emilia; Di Girolamo, Rocco; Maglio, Ornella; Pavone, Vincenzo; Lombardi, Angela; Nastri, Flavia
Abstract: Artificial metalloenzymes as catalysts are promising candidates for their use in different technologies, such as bioremediation, biomass transformation, or biosensing. Despite this, their practical exploitation is still at an early stage. Immobilized natural enzymes have been proposed to enhance their applicability. Immobilization may offer several advantages: (i) catalyst reuse; (ii) easy separation of the enzyme from the reaction medium; (iii) better tolerance to harsh temperature and pH conditions. Here, we report an easy immobilization procedure of an artificial peroxidase on different surfaces, by means of click chemistry. FeMC6*a, a recently developed peroxidase mimic, has been functionalized with a pegylated aza‐dibenzocyclooctyne to afford a "clickable" biocatalyst, namely FeMC6*a‐PEG4 @DBCO, which easily reacts with azide‐functionalized molecules and/or nanomaterials to afford functional bioconjugates. The clicked biocatalyst retains its structural and, to some extent, its functional behaviors, thus housing high potential for biotechnological applications. Abstract : Clickable artificial peroxidase for fast and selective modification of surfaces and nanomaterials.